Do Individuals With Obsessive-Compulsive Disorder and Obsessive-Compulsive Personality Disorder Share Similar Neural Mechanisms of Decision-Making Under Ambiguous Circumstances? - Luo, Yudan; Chen, Lu; Li, Hongchen; Dong, Yi; Zhou, Xiaoqin; Qiu, Linlin; Zhang, Lei; Gao, Yaxiang; Zhu, Chunyan; Yu, Fengqiong; Wang, Kai (Frontiers in Human Neuroscience, 2020)
Impaired decision-making is well documented in obsessive-compulsive disorder (OCD) and a range of electrophysiological and functional neuroimaging measures have begun to reveal the pathological mechanisms that underlie the decision-making process. Obsessive-compulsive personality disorder (OCPD) has core symptoms that often overlap with OCD, but similarities between these disorders at the behavioral and neurological levels are often unclear, including whether OCPD exhibits similar decision-making deficits and shared neurological dysfunction. To address these issues, we examined 24 cases of OCD, 19 cases of OCPD, and 26 matched normal control (NC) subjects during the revised Iowa Gambling Task (IGT) using event-related potentials (ERPs). The net IGT scores were lower for OCD subjects than for OCPD or NC subjects, thus indicating that OCD subjects chose more disadvantageous options and were "short-sighted” with regards to information. The feedback-related negativity (FRN) waveform (lose-win) was larger in both OCD and OCPD subjects. The larger FRN in both OCD and OCPD subjects suggests that obstacles exist in the feedback process. Thus, OCD and OCPD subjects share similar neural mechanisms under ambiguous decision-making circumstances, although OCD subjects exhibit worse behavior performance.